(untitled) (Psychology Travelogs, 2025)
The article derives the results of the study of effective methods of correction and developmental work for the preparation of children with speech impairments for schooling. The study used modern methods and technologies of correction and developmental work with children with speech disorders. The forming stage of the study involved the introduction of special programs of corrective work aimed at improving the speech development of preschool children with speech disorders. The main purpose of this stage was to use effective techniques that would help to improve sound, development of phonemic hearing, enrichment of vocabulary and the formation of connected speech. The programs were developed taking into account the age and individual characteristics of children, which made it possible to optimize the correction process and achieve better results. The first program was based on traditional methods of speech therapy. The main focus was on the production, automation and differentiation of sounds, which is a necessary component of speech development. The second program was based on interactive methods of work and included elements of game therapy. The focus was on creating a speech environment where children could naturally improve their speech skills. In particular, playing speech exercises, articulatory gymnastics, breathing exercises, as well as sensory stimulation methods were applied. Interactive techniques, such as fairytale therapy and role -playing games that contribute to the development of speech in the natural environment, were used. To improve phonemic hearing, exercises were used to distinguish sounds, and to develop connected speech – a method of modeling situations. Particular attention was paid to work with fine motor skills. In the complex, these methods contributed to the increase of the speech readiness of children for school.